PERANCANGAN MEDIA SOSIAL WISATA RELIGI MAKAM MBAH SAYYID DI KELURAHAN BULUSIDOKARE KABUPATEN SIDOARJO - Nurul Azizah; Siti Istikomah; Qouman Sholihin; Dita Wahyu Permata Sari (JAMAIKA: JURNAL ABDI MASYARAKAT, 2022)
This study aims to serve the community in the tourism sector, namely to introduce the tourism potential in Bulusidokare Village, Sidoarjo Regency. Sidoarjo Regency has a lot of tourism potential, one of which is religious tourism to Mbah Sayyid's tomb which is located in Bulusidokare Village RT 12 RW 02. The existence of Mbah Sayyid's tomb is not widely known by people. Therefore, the use of social media is expected to be one way to introduce religious tourism to Mbah Sayyid's tomb. The social media used are Instagram, website, and YouTube.